On Deep Moral Disagreement Between Theists and Atheists. - Bagheri Noaparast, Zoheir (Wittgenstein Studien. Neue Folge, 2025)
The article addresses the deep moral differences between theists and atheists, based on the idea of deep dissent as formulated by Robert Fogelin and Ludwig Wittgenstein. Three types of deep moral differences are identified: those based on moral, non-moral, or metaethical grounds. The author argues that understanding these differences should not be limited to isolated moral beliefs, but must take into account the entire structure of the respective frameworks. Additionally, the divine command theory is examined as an example of a metaethical difference between theists and atheists, highlighting the different moral foundations and their interdependencies.